2011
DOI: 10.1007/s11595-011-0219-z
|View full text |Cite
|
Sign up to set email alerts
|

Gas-solid erosion on bionic configuration surface

Abstract: A three levels orthogonal table-L 9 (3 4 ) was used, namely, impact angle, rotating speed, erodent size, and surface configuration were considered. The three bionic surface configurations are pit, groove, and ring. The experimental results indicate the experiment factors affecting erosive rate are, in their sequence of contribution, erodent size, impact angle, configuration, and rotating speed; the erosive rate increased with increase in rotating speed, erodent size; the erosion resistance of the sample with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The groove cross-section geometric dimensions, viz., H , D , W were selected as the control factors, each at three levels. Reference to the experimental design theory, , the orthogonal array L 9 (3 4 ) was selected to arrange the test program. In conventional full factorial experiment design, it would requires 3 3 = 27 runs to study three parameters each at three levels, whereas orthogonal experimental approach reduces it to only 9 runs offering a great advantage in terms of experimental time and cost.…”
Section: Erosion Testsmentioning
confidence: 99%
“…The groove cross-section geometric dimensions, viz., H , D , W were selected as the control factors, each at three levels. Reference to the experimental design theory, , the orthogonal array L 9 (3 4 ) was selected to arrange the test program. In conventional full factorial experiment design, it would requires 3 3 = 27 runs to study three parameters each at three levels, whereas orthogonal experimental approach reduces it to only 9 runs offering a great advantage in terms of experimental time and cost.…”
Section: Erosion Testsmentioning
confidence: 99%
“…These animals can survive in the solid/gas mixed medium environment, i.e., sand, exhibiting high erosion resistance due to the biological functionality and unique surface texture/morphology [ 91 , 136 , 137 , 138 ]. Hang and Zang et al [ 91 , 136 , 139 ] identified the anti-erosion functionality of the scorpion’s back and the outcomes of multi-coupling effects. Few research studies identified that surface morphology is one of the most critical factors in resisting erosion, i.e., the scorpion resists erosion without causing damage due to its surface morphology [ 136 , 140 , 141 , 142 ].…”
Section: Biomimetic Surfaces Inspired By Animalsmentioning
confidence: 99%
“…However, such practices are not economical. Another alternative method is to add a special structure that changes the flow pattern [6,7]. Researchers control a flow pattern by these structures so as to change the situation in which contact between solid particles and surfaces occur, thereby protecting the materials [8].…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al [12] presented that, due to the grooves of tamarisk surface, tamarisk was protected from sand and wind erosion. A convex pattern and groove were designed and compared with that of a smooth surface to test the property of gas–solid erosion in these studies [6,7,13,14]. Qian et al proved that a convex pattern increased the anti-erosion property and the maximum erosion rate was reduced due to the more dispersed distribution of sand particles around the pressure side and suction side, which caused the number of solid particles impacting the surface to be reduced [15].…”
Section: Introductionmentioning
confidence: 99%